Ostracoda from the Turonian of South-East England Part 2. Cytherocopina. Issue 657 (11th February 2021) - Slipper, I. J.
ABSTRACT: Part 2 is concerned with the Order Podocopida, Suborder Cytherocopina, Superfamily Cytheroidea. The stratigraphic occurrence has been determined by examining 2096 specimens, assigned to 74 species-group taxa arranged in 31 genera. Of these, 40 are referred to previously described taxa, nine species and six subspecies are here described as new, one nomen novum is erected, while 17 taxa are left in open nomenclature, 11 of which are compared to previously described taxa. The Lower Turonian shows a pattern of rapidly increasing richness from 20 to 36 species, followed by periods of stasis and gradually increasing standing richness in the Middle Turonian, rising up to a maximum of 76 species in the Upper Turonian. The platycopid signal hypothesis is rejected as an explanation for the high abundances of cytherellids in the Lower Turonian and isolated younger marls in favour of a more complex solution involving oxygenation, oligotrophy, water depth changes, and diagenetic alteration. Examples of evolutionary patterns are given to demonstrate four cases of loss of ornamentation and one of increase in ornamentation.